2021
DOI: 10.1038/s41598-021-99081-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum activin A levels and albuminuria among community-dwelling middle-aged and older adults in Taiwan

Abstract: Activin A, a cytokine belonging to the transforming growth factor-β family, has been shown to play pivotal roles in tissue remodeling after renal injury and is present in elevated levels in diabetic patients. However, the association between activin A and albuminuria remains unclear. We aimed to evaluate their association by using cross-sectional data from community-dwelling middle-aged and older adults in Taiwan. We assessed 466 participants (67% male; mean age 71 ± 13 years) from the I-Lan Longitudinal Aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The importance of activin in CKD is gradually increasing in various renal diseases and their complications. Previous studies have demonstrated that activin is a pro-cachectic factor and a potent activator of renal interstitial fibrosis and matrix protein production in mesangial cells [14‒16]. In KT patients, previous studies have reported an increase in activin levels in allografts during ischemia-reperfusion injury and alternate macrophage activation (M2 phenotype) [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of activin in CKD is gradually increasing in various renal diseases and their complications. Previous studies have demonstrated that activin is a pro-cachectic factor and a potent activator of renal interstitial fibrosis and matrix protein production in mesangial cells [14‒16]. In KT patients, previous studies have reported an increase in activin levels in allografts during ischemia-reperfusion injury and alternate macrophage activation (M2 phenotype) [17, 18].…”
Section: Introductionmentioning
confidence: 99%